Catalytic decomposition of organic peroxides in non-aqueous media under metal-free nanoporous and nanosized carbocatalysts - K. V. Voitko; O. M. Bakalinska; M. T. Kartel (Хімія, фізика та технологія поверхні)
The aim of this study is to investigate the catalytic system “Carbon nanomaterial-diacyl peroxide molecule-non-aqueous medium” and determine main factors that influence on carbon catalyst’s effectiveness. The catalytic activity of nanoporous (activated carbon (AC)) and nanosized (multiwalled carbon nanotubes (CNT)) carbon catalysts and their modified forms were investigated in the decomposition of benzoyl and lauroyl peroxides (BP and LP respectively) at room temperature in non-aqueous media by measuring the volume of released CO2. As the decomposition of BP and LP strongly depends on the solvent, the selection of “inert” one was based on preliminary results. Ethyl acetate and tetrachloromethane were used for BPD and LPD, respectively. Among factors that determined the catalytic performance of investigated samples their structural-sorption properties, surface chemistry and diffusion limitation have been considered. It was established that in spite of the high surface area of AC they show moderate catalytic activity comparing to CNT because of internal diffusion limitation. As a consequence, their activity is determined by the textural characteristic of carbon matrices. Catalytic performance of the CNT samples exceeds of AC in 2–20 times. Based on the calculated diffusion coefficients it was concluded that catalysis by CNT is carried out in the kinetic region on their accessible surface. Such catalytically active surface has a lot of N-containing functional groups as well as basic O-containing ones, therefore it shows better activity towards organic peroxides. Moreover, CNT’s surface is more hydrophobic that is promoting the reaction proceeding in non-aqueous media. The decomposition rate of steric BP is lower compared to the long chain of LP (in both cases of AC and CNT). Based on this finding, it could be predicted that mesoporous CNT with high content basic functionalities and good surface accessibility should be the excellent catalyst for diacyl peroxides decomposition in organic solvents.